Thio(Urea) derivatives : from anion sensing and recognition towards supramolecular assemblies - Boyle, Elaine M. (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
This thesis entitled (Thio)Urea Derivatives - From Anion Sensing and Recognition to Supramolecular Assemblies consists of seven chapters. Chapter 1 provides an introduction to the field of anion sensing using various organic scaffolds incorporating the thio(urea) moiety. The importance of anion sensing and the challenges associated with the development of receptors for the recognition of anions are detailed. An overview of the recent developments in the field is also given. The second half of the introduction focuses on the development of interlocked assemblies with a particular emphasis on rotaxanes. Finally, a summary of the work described in this thesis is outlined.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.